DETERMINAN MOTIVASI KERJA DAN IMPLIKASINYA TERHADAP KOMITMEN PEGAWAI PUSDIKLAT KEMENTERIAN AGAMA REPUBLIK INDONESIA - Sairin Sairin; Hadyati Harras (Sekolah Menengah Kejuruan (SMK) Pustek, 2020)
The state civil apparatus is a state servant in charge of serving the community. Therefore, they are required to work professionally and integrity. To achieve good performance requires an attitude of commitment, and this is influenced by many factors including leadership, organizational culture, and work motivation. This study aims to analyze these three factors, how they affect commitment. Research methods using quantitative and path analysis. The research site at Education and Training Center of Indonesian Religion Ministry. The unit of analysis sampled was 50 people (employees who volunteered to fill out the questionnaire). The results showed that organizational culture can significantly increase employee commitment if work motivation to be mediation